Distribución geográfica del gasto municipal en la provincia de Maynas periodo 2020 – 2022 - Tangoa Macuyama, Sandrita Haymeth (2024)
The general objective of the study is to identify how the geographical distribution of municipal spending is presented in the province of Maynas for the period 2020 - 2022, using a descriptive quantitative methodology and a non experimental design, with the budget records of the municipalities located as population. In the geographical area under study, the research concluded that in the province of Maynas, a marked inequity is evident in the distribution of both current spending and capital spending, in the first case, the disparity between the different areas stands out. , such as the low percentage assigned to Alto Nanay (1.8%) compared to the significant 41.2% allocated to Iquitos, similarly, in capital spending, an unequal distribution is observed, with Iquitos being the main beneficiary with 44.4%, while other areas such as Torres Causana receive only 2.0%, in addition, in terms of municipal spending, inequality is highlighted, highlighting that San Juan Bautista receives a notable 20%, while Torres Causana only 2%, in addition, the distribution Geographical analysis of municipal spending reveals persistent inequities between urban and rural districts throughout the years 2020, 2021 and 2022. Consequently, it is suggested to implement corrective measures, review allocation criteria and consider policies that address the specific needs of each area to achieve a more equitable distribution of resources.